2012
DOI: 10.1101/gad.184911.111
|View full text |Cite
|
Sign up to set email alerts
|

E2F7, a novel target, is up-regulated by p53 and mediates DNA damage-dependent transcriptional repression

Abstract: The p53 tumor suppressor protein is a transcription factor that exerts its effects on the cell cycle via regulation of gene expression. Although the mechanism of p53-dependent transcriptional activation has been well-studied, the molecular basis for p53-mediated repression has been elusive. The E2F family of transcription factors has been implicated in regulation of cell cycle-related genes, with E2F6, E2F7, and E2F8 playing key roles in repression. In response to cellular DNA damage, E2F7, but not E2F6 or E2F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
127
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 54 publications
4
127
0
Order By: Relevance
“…In this paper, we determined a pathway by which DENmediated liver cancer eliminates this pathway. Another target of p53 within the cell cycle is E2F7 (20). We found that CUGBP1-C/EBP␤-HDAC1-mediated repression of p53 also reduces levels of E2F7.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In this paper, we determined a pathway by which DENmediated liver cancer eliminates this pathway. Another target of p53 within the cell cycle is E2F7 (20). We found that CUGBP1-C/EBP␤-HDAC1-mediated repression of p53 also reduces levels of E2F7.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, it operates as a dominant negative molecule by binding to DNA and inhibiting activities of other members of E2F family, leading to inhibition of cell proliferation. It has been shown recently that p53 up-regulates transcription of E2F7 and that this activation contributes to p53-dependent growth arrest (20). Quantitative RT-PCR and Western blotting showed that both mRNA and protein levels of p21 and E2F7 are reduced at 10 and 30 weeks after DEN treatments (Fig.…”
Section: The P53-p21 and P53-e2f7 Pathways Of Inhibition Of Liver Promentioning
confidence: 99%
“…The correct regulation of the E2F7 alternative exon is likely important for the cell, because use of the exon changes the reading frame and alters the C terminus of the protein, which is necessary for the transcriptional activation of its target genes. E2F7 has antiproliferative properties (61,62), and it is possible that SNORD27 changes observed in cancer influence E2F7-dependent cell cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…ChIP-sequencing analysis reveals that E2F7 binds to multiple G 1 /S-regulated genes and represses their transcription (16). E2F7 is induced by p53 and is involved in cell cycle arrest response to DNA damage and cellular senescence (17)(18)(19). Recent studies using mouse model systems also show that the atypical E2Fs are involved in angiogenesis, polyploidization, and placental development (20 -23).…”
mentioning
confidence: 99%